(untitled) (Global Journal of Medical Research, 2024)
Introduction Neuropathic pain is one of the reasons for intervention in diabetic patients and photobiomodulation PBM is a non-pharmacological therapeutic alternative which has been increasingly used in recent years with modulatory actions on cellular energy metabolism Objective To evaluate the acute effect generated by photobiomodulation with light emitting diode LED on pain in individuals with neuropathy resulting from type 2 diabetes mellitus Methods The study consisted of the evaluation of the signs and symptoms of neuropathic pain Douleur Neuropathique Questionnarie DN4 and blood flow in the posterior and dorsal tibial arteries Doppler ultrasound after the application of PBM for three consecutive days in 58 patients